Plant Growth-Promoting and Herbicidal Bacteria as Potential Bio-Based Solutions for Agriculture in Desertic Regions - Patricio Muñoz-Torres; Wilson Huanca-Mamani; Steffany Cárdenas-Ninasivincha; Yola Aguilar; Antonio Quezada; Franco Bugueño (Plants)
The region of Arica and Parinacota hosts unexplored remote sites with unique characteristics suitable for developing novel agricultural bioproducts. Notable locations include Jurasi Hot Springs, Polloquere Hot Springs, and Amuyo Lagoons, featuring open pools fed by thermal mountain springs. These geothermal sites harbor bacteria with plant growth-promoting activities, particularly interesting to the strains J19, TP22, A20, and A3. These bacteria possess in vitro plant growth-promoting traits, the ability to produce hydrolytic enzymes, and the capacity to inhibit phytopathogenic fungi. Moreover, they can tolerate different concentrations of NaCl and boron, making them suitable for developing new agricultural bioproducts for arid environments. The bacterial strains A3 and A20 have a positive effect on the growth of the aerial part of tomato plants (increased stem length, fresh and dry weight), with a significant increment in proline concentration and chlorophyll A and B content under saline conditions. Meanwhile, the strains J19 and TP22 exhibit herbicidal activity against Cenchrus echinatus by reducing root elongation and germination of the weed. These strains possess plant growth-promoting traits and improve plant resistance to salinity stress. They are promising candidates for developing innovative bio-based agricultural products suited to arid and semi-arid regions.